Association between interleukin-32 gene polymorphism and susceptibility to preeclampsia: Running Head: Association of IL-32 and preeclampsia - Fatemeh Mazlum; Behrouz Gharesi-Fard; Hossein Hadinedoushan; Yousef Bakhshizadeh Ghashti (Taylor & Francis Group, 2021)
Objective: To determine association between IL-32 gene polymorphism, and serum levels of IL-32 and susceptibility to preeclampsia (PE). Methods: The frequency of IL-32 rs9927163 and rs4786370 polymorphisms was determined by PCR-RFLP. Also ELISA was used to determine the levels of serum IL-32. Results: Regarding rs4786370 C/T SNPs, the frequencies of CT, TT genotypes, and T allele were shown to be higher in the PE patients. IL-32 serum level significantly increased in the PE patients. Conclusion: Variety of allele and genotype IL32 rs4786370 as well as a rise in serum level of IL-32 can be regarded as a risk factor for PE.